2008
DOI: 10.1021/bi800289w
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Putative Helix−Helix Interacting GxxxG-Motifs and Tryptophan Residues in the Two-Peptide Bacteriocin Lactococcin G

Abstract: The membrane-permeabilizing two-peptide bacteriocin lactococcin G consists of two different peptides, LcnG-alpha and LcnG-beta. The bacteriocin contains several tryptophan and tyrosine residues and three putative helix-helix interacting GxxxG-motifs, G 7xxxG 11 and G 18xxxG 22 in LcnG-alpha and G 18xxxG 22 in LcnG-beta. The tryptophan and tyrosine residues and residues in the GxxxG-motifs were altered by site-directed mutagenesis to analyze the structure and membrane-orientation of lactococcin G. Substituting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 53 publications
(98 reference statements)
2
55
0
Order By: Relevance
“…It has been speculated previously that the two-peptide bacteriocins recognize target cells through a receptor in the target cell membrane (26). Recently, it was shown that a component of the mannose phosphotransferase system (mannose-PTS) is the target cell receptor for several class II bacteriocins such as lactococcin A and the pediocin-like bacteriocins (9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been speculated previously that the two-peptide bacteriocins recognize target cells through a receptor in the target cell membrane (26). Recently, it was shown that a component of the mannose phosphotransferase system (mannose-PTS) is the target cell receptor for several class II bacteriocins such as lactococcin A and the pediocin-like bacteriocins (9).…”
Section: Resultsmentioning
confidence: 99%
“…Lactococcin G is perhaps the best-characterized two-peptide bacteriocin (12,18,19,21,24,26,27). It consists of the 39-residue ␣ peptide (termed Lcn-␣) and the 35-residue ␤ peptide (termed Lcn-␤) (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For both class I and class IIa bacteriocins, these residues have frequently been found to play an important role in mediating the initial interaction with the anionic target cells via electrostatic interactions (3,4,17). Indeed, recent studies with the most extensively studied class IIb bacteriocin, lactococcin G, also revealed an important role for such residues in positioning the cationic C termini of the bacteriocin components inside the target cell (23,25,27). Here, we sought to maintain the potent antilisterial activity of the salivaricin P components while establishing a trypsin-resistant phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, engineering of a bacteriocin to reduce its sensitivity to proteases is also a viable option. Engineering of bacteriocins has been used to generate variants which have helped scientists to better understand the structure-function relationships of these peptides (6,7,10,11,14,24,25,28,31,34), and there have been recent successes in which the antimicrobial activity of bacteriocins has been enhanced through a bioengineering-based approach (1,8,9,15,17,19,35). Despite this, bioengineered peptides with enhanced protease resistance have been generated only in the case of the class I bacteriocin gallidermin.…”
mentioning
confidence: 99%